2015
DOI: 10.1111/coep.12157
|View full text |Cite
|
Sign up to set email alerts
|

Mass Layoffs, Manufacturing and State Business Climates: Does State Policy Matter?

Abstract: This study provides the first estimates on the relationship between state public policies and job losses in the manufacturing sector. In addition, spatial model estimation is adopted to identify any effect that state policies may have on the adopting state as well as upon neighboring states. We find evidence that favorable ratings regarding some elements of a state's business climate coincide with a lower incidence of job loss. This relationship holds beyond the adopting state and is correlated with lower job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Similar results were explored also by Fereidouni and Masron [31]. Likewise, Surfield and Reddy [36] found that business climate coincides with a lower rate of job loss. According to Blume [37], the local economic policies are associated with the business climate.…”
Section: Literature Reviewsupporting
confidence: 77%
“…Similar results were explored also by Fereidouni and Masron [31]. Likewise, Surfield and Reddy [36] found that business climate coincides with a lower rate of job loss. According to Blume [37], the local economic policies are associated with the business climate.…”
Section: Literature Reviewsupporting
confidence: 77%